SISTEM AKUNTANSI PEMERINTAH DAERAH DAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH SURABAYA : SEBUAH TINJAUAN TEORITIS - Setyowati, Edyta Dwi; Wulandari, Putri; Yantino, Arnaldo; Narastri, Maulidah (Universitas 17 Agustus 1945 Surabaya, 2021)
This article aimed to present the implementation of the local government accounting system and the performance accountability of government agencies. This article specifically discussed the implementation of the Surabaya city government. The method used literature review, so the authors review or review precious studies through literature sources in the form of international and national journals. The results showed that the local government accounting system with performance accountability in Surabaya city government agencies had an effect on financial reports.